Study of Corrosion Inhibition for Some New Schiff Bases Synthesized from Quinazolinone Derivative - Mohammed, Aseel Jassim; Al-Jeilawi, Oday H. R. (Iraqi Journal of Science, 2024)
In this work, new Schiff bases of quinazolinone derivatives (Q1-Q5) were synthesized from methyl anthranilate. The synthesis involved three steps. In the first step, methyl anthranilate was reacted with isothiocyanatobenzene, producing the thiourea derivative K1. The second step entailed reacting K1 with hydrazine hydrate, synthesizing 3-amino-2-(phenylamino) quinazolin-4(3H)-one (K2). The third step involved reaction of K2 with various aromatic aldehydes, yielding the Schiff bases derivatives Q1-Q5. The chemical structures of these compounds were identified by FT-IR,1H NMR and 13C NMR spectroscopy. The newly synthesized derivatives (Q1-Q5) were subjected to rigorous evaluation to assess their efficacy as corrosion inhibitors for carbon steel in an acidic environment (1M HCl). Weight loss measurements were employed, and the concentration of the compounds was varied to gauge their performance at ambient temperature. Among the array of compounds tested, Q1 exhibited remarkable performance, particularly when employed at a concentration of 0.5 M. The corrosion inhibition properties of compound Q1 were evaluated. It exhibited excellent inhibition efficiency, reaching a peak of 93% according to the investigation. Further dynamic polarization analysis revealed some interesting relationships between inhibition efficiency, concentration, and temperature. Specifically, higher concentrations and lower temperatures led to enhanced inhibition by Q1.